1960
DOI: 10.1126/science.132.3443.1895
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-65 and Chromium-51 in Foods and People

Abstract: Some radioisotopes introduced into the Columbia River via effluent water from reactors at Hanford, Wash., are found in crops irrigated with this water and in sea food harvested near the mouth of the river. Measurements of zinc-65 and chromium-Si in foods and in individuals consuming these foods are reported and are compared with zinc-65 concentrations resulting from fallout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1962
1962
1987
1987

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…is widespread in the marine environment and has been detected in various organisms by many investigators (Robertson, 1968;Folsom, et al, 1963;McCauley, 1971;Nagata and Folsom, 1954;Osterberg, et al, 1964;Perkins, et al, 1960;Watson, et al, 1961;Wolfe, 1970;Young and Folsom, 1967 Zn by diatoms and Chelex-100 chelating resin occurred at different rates, and that equilibration between the zinc and the 65 Zn was slow relative to biological uptake (see Figure 3). The obvious explana-65 tion is that the zinc and Zn were present in the seawater culture medium in Zn from the crabs.…”
Section: Zinc -^^Znmentioning
confidence: 97%
“…is widespread in the marine environment and has been detected in various organisms by many investigators (Robertson, 1968;Folsom, et al, 1963;McCauley, 1971;Nagata and Folsom, 1954;Osterberg, et al, 1964;Perkins, et al, 1960;Watson, et al, 1961;Wolfe, 1970;Young and Folsom, 1967 Zn by diatoms and Chelex-100 chelating resin occurred at different rates, and that equilibration between the zinc and the 65 Zn was slow relative to biological uptake (see Figure 3). The obvious explana-65 tion is that the zinc and Zn were present in the seawater culture medium in Zn from the crabs.…”
Section: Zinc -^^Znmentioning
confidence: 97%
“…The cooling water was t aken from and released back into the Columbia River. A study (Perkins et al . 1960) indicated that the principal routes of human intake of zinc -65 were from Columbi a River drinking wate r , fish, and seafood.…”
Section: -mentioning
confidence: 99%
“…T h e p a t t e r n of deposition d o e s indeed follow that ( 3 ) , M i n i m u m deposition o c c u r s at the p a r t i c l e s i z e upon which the D a t a of W i l s o n and L a M e r ( 4 ) a r e given i n F i g u r e 4.…”
Section: T T R I B U T E D T O H Y G R O S C O P I C I T Y S I N C E mentioning
confidence: 99%
“…-A mixture of concentrated n i t r i c , s u l f u r i c and perchloric acids was used i n the wet digestion of t i s s u e specimens, since t h i s medium has been successfully applied i n t h e d i s s o l u t i o n of other biological samples (3). media was normally complete within one hour using t h e q u a n t i t i e s of t i s s u e mentioned above.…”
mentioning
confidence: 99%